Effect of Dopants and Mechanochemical Treatment on Vanadium Phosphate Catalysts For Partial Oxidation of N-Butane to Maleic Anhydride - Sairi, Nor Asrina (2007)

(untitled)
Oxidation of n-butane to maleic anhydride catalyzed by vanadium phosphate catalyst is one of significant worldwide commercial interest since decades. Introductions of dopants and/or mechanochemical treatment are the most promising approach for the improvement of the catalytic performance of vanadium phosphate catalyst. Tellurium doped vanadium phosphate catalyst (VPDTe) was prepared via VOPO4·2H2O phase after calcinating the tellurium doped precursor, VOHPO4•0.5H2O at 733 K in a flowing of n-butane/air for 18 h. VPDTe catalyst gave very high for n-butane conversion, 80% compared to only 47% for the undoped catalytst. The crystallite size, morphology, surface reactivity and reducibility of the catalyst have been affected by the addition of tellurium. VPDTe catalyst has result a higher existence of V5+ phase in the catalyst bulk with having nearly the optimum amount of V5+/V4+ ratio, 0.23. The SEM micrographs showed that the tellurium altered the arrangement of the platelets from “rose-like” clusters to layer with irregular shape. The sizes of platelets are even thicker and bigger which led to lower surface area compared to undoped VPD catalyst. An addition of 1% tellurium has markedly lowered the reduction activation energies of the vanadium phosphate catalyst as revealed by TPR profiles. The amount of oxygen species removed from the peak associated with V4+ phase for VPDTe catalyst significantly higher. These phenomenon suggested that the O=V bond of the VPDTe catalyst are weaker with higher mobility and more reactive of the oxygen as compared to the undoped counter part. All mechanochemial treated VPD catalysts have shown an increased surface P/V ratio, reduced the crystallite size of the catalysts and displayed different degree of crystallinity. TPR results demonstrated that both reduction peaks for every mechanochemical treated catalyst shifted to lower temperature and improved the amount of oxygen removed from the catalysts. VPDM catalyst gave 57% of conversion, 10% higher from the untreated VPD catalyst. The presence of cobalt in mechanochemical treated vanadium phosphate catalyst has slightly lowered the n-butane conversion to 54%. Meanwhile, treating the tellurium doped catalyst through mechanochemical treatment i.e. milling in stainless steel (VPDTeM) or agate (VPDTeM-ag) with ethanol as solvent has reduced the conversion from 80% to 58% and 50%, respectively. The selectivity of all catalysts prepared was almost retained in all cases (~ 33%) except for VPDCoM catalyst (19%).